On the difference in defluoridation performance of interchanging polyvinyl alcohol coated layer in poly (piperazine-amide) composite membranes - Jhanvi Lakhani; Mayank Saxena; Amit Bhattacharya (Desalination and Water Treatment)
Triple-layer membranes were prepared using a combination of poly(piperazine-amide), poly(vinyl alcohol), and polysulfone membranes. The poly(piperazine-amide) and poly(vinyl alcohol) layers are coated alternately and vice-versa on polysulfone membranes. The effects of changing the sequence of the PVA-MA layer in the three-layer system of poly(piperazine-amide) composite membranes on physical parameters (viz. surface roughness, water contact angle, and zeta potential) of the skin layer were studied. The separation performances of triple-layer membranes were evaluated through pure water flux and defluoridation. Scanning electron microscopy (SEM), and atomic force microscopy (AFM) measurements were utilized for visual characterization of modified membranes. The defluoridation performances of Memb-I, (R% 91, PVA-MA serves as the inter-layer) were always better compared to Memb-II R% 77.4, in which PVA-MA served as the surface layer. The defluoridation performances of membranes of both types decreased as the total dissolved solutes (TDS) increased of water matrices (water matrix-I > water matrix-II > water matrix- III). The time-dependence defluoridation performance suggested that there was little deterioration in separation and more downtrend followed as the TDS of water matrices increased.